Pendampingan Penerapan Model Pembelajaran RME Berbasis Etnomatematika Bagi Guru di SDN 06 Desa Tapak Gedung - Neza Agusdianita; Adhadi Kurniawan; Intan Zoraya; Yusnia Yusnia; Rizqa Dwi Shofiya Maghfira Izania; Sovia Lorenza; Debi Heryanto (FKIP Universitas Sebelas Maret, 2025)
The Realistic Mathematics Education (RME) approach based on ethnomathematics has been introduced as a significant innovation in mathematics teaching in primary schools, linking mathematical concepts with local culture and students' daily lives. The objective of this service initiative is to enhance teachers' competencies in implementing RME, as well as to make mathematics learning more engaging and meaningful for students. The methods employed in this service initiative include training and mentoring for teachers, consisting of seminars, discussions, and direct teaching practices. The results of this initiative indicate a significant improvement in teachers' knowledge and skills in utilizing the RME learning model. Evaluation shows that the average student scores increased from 60.25 in the pretest to 91.25 in the posttest, indicating the success of this method's implementation. The conclusion drawn from this activity is that continuous mentoring for teachers in integrating ethnomathematics into RME learning is crucial for enhancing the quality of mathematics education, especially in the context of local culture. The application of this model not only improves students' understanding of the material but also fosters their interest in mathematics as a whole.